Biomarkers for Early Detection of Lung Cancer - Vaidya, Vinit; Bhandary, Vedaant; Vishwakarma, Priyanshi; Qureshi, Faisal (Research Developments in Medicine and Medical Science Vol. 3, 2023)
Lung Cancer is one of the leading causes for cancer related deaths with a 5-year survival rate of only 18%.These are broadly divided into 2 types: NSCLC (non-small cell lung cancer) and SCLC (small cell lung cancer) and although treatments like chemotherapy, targeted treatments are commonly used, the survival rate is still very poor due to the late detection of these cancers. Biomarkers are naturally occurring biological genes which show changes when a tumor formation takes place. Various experimental and research data was retrieved from search engines like PubMed, Google Scholar etc. Our article provides an overview of lung cancer, its therapies, and mainly concentrates on potential biomarkers that could aid in the early detection of lung cancer.